Determination of Methomyl Residues in Bohe by Ultrahigh-Performance Liquid Chromatography-Tandem Mass Spectrometry (UPLC-MS) - Yao Zheng; Addotey Tracy Naa Adoley; Benkhelifa Fateh; Wei Wu; Gengdong Hu; Liping Qiu; Jiazhang Chen (International Journal of Analytical Chemistry)
The aim of this work is to investigate the presence of methomyl pesticide residue and the rate of disappearance in mint cultivated in the aquaponics system based on the application of UPLC-MS to establish a safety time interval before crop harvesting. Results showed that an effective and sensitive method based on UPLC-MS has been used for the determination of methomyl pesticide residues in mint. The initial residue level was much higher in roots (79.52 μg/kg), and it can be decreased to 16.73 (after 15 days) μg/kg and 3.31 (20 days) μg/kg, while the least was detected on the mix leaves and stems (44.54 μg/kg), and it can be decreased to 15.35 (after 20 days). In our case, we suggest that a safety interval in the range of 15–20 days should be allowed after the detection of methomyl in water, and the concentration of methomyl was lower than the acceptable daily intake (ADI) of the China Food and Drug Administration (CFDA) (20 μg/kg).